ANALISIS PEKERJA PEREMPUAN DAN PENGARUHNYA TERHADAP PENDAPATAN KELUARGA: Studi Kasus Pedagang Perempuan di Pasar Aur Duri Kota Jambi - Neni Triana (Harakat an-Nisa: Jurnal Studi Gender dan Anak, 2021)
This study aims to determine the social and economic characteristics of women who trade in the Aur Duri Market in Jambi City. This study uses quantitative methods with multiple regression analysis tools. The results showed that the variables of age, working hours, number of children, and level of education together had a significant effect on the income variables of women who traded. Meanwhile, partially the age variable has a positive and significant effect on the income of women who trade, while the variable number of children has a negative and signific effect on the income of women who trade. The variables of working hours and level of education did not have a significant effect on the income of women who traded.